Application of microwave six-port in software radio - ZHANG Lan1; WANG Bing2; FENG Ke-jin1 (Tongxin xuebao)
Common formulas of six-port demodulation orthogonal modulation signals was educed. The results of simulation in demodulation QPSK, 16QAM, π/4QPSK modulation signals are well agreement with the theory analysis. Moreover, the influence of the character of 90°hybrid bridge in six-port was studied. For QPSK signal , the result imply demodulation characteristic degrade less 0.5dB when amplitude unbalance is less than 0.3dB and phase unbalance is less than 3°.